1996
DOI: 10.1093/nar/24.10.1855
|View full text |Cite
|
Sign up to set email alerts
|

The basic domain/leucine zipper protein hXBP-1 preferentially binds to and transactivates CRE-like sequences containing an ACGT core

Abstract: The transcription factor hXBP-1 belongs to the family of basic region/leucine zipper (bZIP) proteins and interacts with the cAMP responsive element (CRE) of the major histocompatibility complex (MHC) class II A alpha, DR alpha and DP beta genes. However, the developmental expression of hXBP-1 as revealed by in situ hybridization in mouse embryos, has suggested that it interacts with the promoter of additional genes. To identify other potential target genes of this factor, we performed binding site selection ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 20 publications
4
98
0
Order By: Relevance
“…It is interesting to note that XBP-1 interacts with cAMP-responsive elements of many genes and activates their expression (33). Because the cAMP pathway is essential for memory formation (34), our data suggest a putative role for the XBP-1 transcription factor in learning and memory mechanisms.…”
Section: Late Gene Expression Changes Of Mice In Enriched Environmentmentioning
confidence: 77%
“…It is interesting to note that XBP-1 interacts with cAMP-responsive elements of many genes and activates their expression (33). Because the cAMP pathway is essential for memory formation (34), our data suggest a putative role for the XBP-1 transcription factor in learning and memory mechanisms.…”
Section: Late Gene Expression Changes Of Mice In Enriched Environmentmentioning
confidence: 77%
“…To identify genes specifically involved in the recognition and degradation of misfolded SP-C, we searched for potential XBP-1 target genes, because this transcription factor modulates expression of several key genes in the ERAD pathway. Analysis of the 5Ј-flanking sequence of genes induced by mutant SP-C identified Ͼ1000 genes with at least one TGACGTGR motif (UPRE) associated with XBP-1 binding (Clauss et al, 1996;Yoshida et al, 2001;Kanemoto et al, 2005;Acosta-Alvear et al, 2007;Shen and Hendershot, 2007); interrogation with other recently identified XBP-1 binding motifs would likely increase this pool (Acosta-Alvear et al, 2007). Genes encoding ER proteins were identified by database annotation, and the number of candidate genes was subsequently increased by literature search and use of algorithms predicting ER localization.…”
Section: Discussionmentioning
confidence: 99%
“…We discuss here only the human X-box binding protein-1 (XBP-1) and the nras-related gene. XBP-1 is a member of the ATF/CREB transcription factor family that activates promoters containing CREs (Clauss et al, 1996). During liver regeneration, XBP-1 is associated with increased proliferation and reduced apoptosis (Reimold et al, 2000), implying a survival function that may explain the role of its overexpression in hepatocellular carcinomas (Kishimoto et al, 1998).…”
Section: Candidate Genesmentioning
confidence: 99%
“…Overexpression of NPM may eliminate the remaining IRF-1 activity, blocking its ability to initiate an apoptotic caspase cascade, and/or induce p21 waf/1cip1 (Coccia et al, 2000) and cooperate with p53 in signaling to growth arrest and apoptosis (Tanaka et al, 1994a(Tanaka et al, , 1996. XBP-1 acts through its ability to regulate genes containing CRE in their promoters (Clauss et al, 1996). A cAMP-dependent pathway that inhibits IRF-1 transactivation has been described (Delgado et al, 1999); XBP-1 activation of this pathway could suppress further the already low IRF-1 activity in some antiestrogen-resistant cells.…”
Section: One Component Of a Gene Networkmentioning
confidence: 99%